Cegah Stunting dengan Penyuluhan Gizi Seimbang pada Masa Menyusui di Desa Sukamulya Kecamatan Singaparna - Tupriliany Danefi; Lilis Lisnawati (Yayasan Inspirasi El Burhani, 2023)
Introduction: Optimal nutritional intake during the breastfeeding mother phase is one way to prevent stunting in toddlers in the future. This is part of preventing stunting in the first 1000 days of birth. One of the direct causes of stunting in toddlers is malnutrition during the first 1000 days of a child's life. Therefore, stunting prevention needs to start when women are pregnant, breastfeeding and until the child is 2 years old. Objective: this community service activity is to increase the understanding and knowledge of breastfeeding mothers about balanced nutrition during breastfeeding. Method: This community service activity was carried out in a toddler class in Sukamulya Village. By first carrying out the pre test and after carrying out the counseling the implementation of the post test is to measure the extent to which the effectiveness of the implementation of the counseling given. The target was breastfeeding mothers in Sukamulya Village, Working Area of ​​the Singaparna Health Center, a total of 41 people. Result: The results obtained were 19 people (46.3%) experienced an increase in scores from pre-test to post-test and those who experienced a decrease were 7 people (17.1%), with the same value of 15 people (36.6%) and an increase in knowledge in the good category from 95.1% to 97.6%. Conclusion: Based on the results of these activities it can be interpreted that balanced nutrition counseling activities during breastfeeding are quite effective for increasing knowledge.